PENGARUH BEBAN TANGGUNGAN, PENGANGGURAN, DAN PENDIDIKAN TERHADAP KEMISKINAN DI NUSA TENGGARA TIMUR - Siagian, Fenny Elfride; Budhi, Made Kembar Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Poverty is a multidimensional problem that can be experienced by society. Some of the causes of poverty due to low education, low levels of health, and limited employment opportunities. The purpose of this study was to determine the effect of simultaneously and partially Dependent Burden, Unemployment, and Education on poverty in the Regency/City of East Nusa Tenggara Province. This study uses secondary data with panel data analysis, which consists of 2016-2020 time series data and cross section data of 23 regencies/cities in East Nusa Tenggara Province. The results of the research using the fixed effect model show that dependents have a positive and significant effect on poverty, unemployment has no significant effect on poverty and education has no significant effect on poverty in East Nusa Tenggara Province.